Revealing diversity among narratives of agricultural transformation: insights from smallholder farmers in the Northern Kilombero Valley, Tanzania - Lala, Margherita; Sallu, Susannah M.; Lyimo, Francis; Moore, Eleanor; Shirima, Deo D.; Nnyiti, Petro; Mwanga, Lilian; Pfeifer, Marion (Frontiers in Sustainable Food Systems, 2023)
The discourse of transformation, as currently adopted in policy arenas, has given scarce attention to diverse knowledges, plural pathways, and politics. Narratives about change and agricultural transformation in African landscapes are diverse. However, failure to recognise diversity among narratives of the predominant food producers – smallholder farmers – in planning and policy processes limits potential to achieve just agricultural transformation. To progress understanding on diverse knowledges, plural pathways, and politics of agricultural transformation in this paper we present smallholder visions of future farms and their narratives of agricultural transformation in an African landscape subject to rapid ecological and livelihood change. We present smallholder narratives of transformation alongside those promoted by national and private-sector blueprints, and critically reflect on the social justice of transformation. From nine participatory workshops conducted with smallholder farmers in the northern Kilombero Valley of the Southern Agricultural Growth Corridor of Tanzania (SAGCOT), four main narratives of transformation were identified: (1) land ownership, (2) expansion of agricultural activities, (3) diversification, and (4) access to water for irrigation. The view of transformation presented by smallholders appears incompatible with national blueprint policies and plans. Despite ‘win-win’ narratives of transformation and the outgrower scheme approach to expansion of sugarcane cultivation promoted by SAGCOT, the national government and the Kilombero Sugar Company, we found that land ownership and expansion remains challenging for smallholders in the present and represents a key aspiration for the future, along with diversification and access to adequate amounts of water for irrigation. These visions of bigger, more diverse farms with access to water, are not necessarily compatible with the expansion of sugarcane cultivation in the area and does not appear, as yet, to be sufficiently recognised in sugarcane expansion plans, creating potential to exacerbate injustice. We demonstrate the need for greater effort among actors in rural African landscapes to realise and recognise the diversity and contextuality of envisaged desirable futures in plans and polices, and the importance of progressing understanding on inclusive planning and policy-making processes to achieve inclusive negotiation leading to more just transformation pathways.